Clean craftsmanship : disciplines, standards, and ethics : (companion videos) (Addison-Wesley Professional, 2021)
These videos are meant to be used with the book: Clean Craftsmanship: Disciplines, Standards and Ethics. The videos demonstrate the code examples in Chapters 2 and 3 on TDD. We recommend that you access the book in a new tab to view the companion videos with the book.